Design of Smart Vehicle to Detect Unauthorized Access and Theft Detection - Cornelius , K.; Shanthini , B.; Brindha , S.; Prakash , J. Jaya; Kumar , M. Sasi; Kumar , K. T. Nivas (Theory and Applications of Engineering Research Vol. 6, 2024)
In the current global context, security of cars in public parking lots, in particular, has become a major concern. With the use of global positioning system (GPS) and global system for mobile communication (GSM) technology, this system enforces simple and affordable vehicle following. the majority of the system's components, including the RFID reader, IR sensor, GPS module, GSM modem, and microprocessor. The purpose of the GPS system is to track the vehicle's location. While the GPS system is the only one that receives vehicle location data from satellites, the GSM system is also installed in the car to provide data to the owner of the vehicle. In the event that the car needs to be towed or breaks open, this method automatically sends an SMS with a speedometer.